Prediksi Persediaan Galon dan Gas Pada Toko Mu’afah Menggunakan Metode Weighted Moving Average - Lailatul Fitria; Nuris Sayyidatul Fatimah; Triyunita Nur Hayati; Soffiana Agustin (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
Indonesian people are very dependent on bottled mineral water resources (gallons) and LPG gas for their daily needs. The dependence on these two resources provides a great opportunity for business people to sell gallons and LPG gas. Mu’afah shop is a basic food store that provides all household needs for daily use, one of the needs sold is gallons and lpg gas. Sales of gallons and lpg gas are erratic in this store, sometimes in a day the sales are very high but it can also be that in a day there is no single sale. This makes the seller unable to ensure the right time to restock goods. This research is qualitative using the weight moving average method with mu’afah shops as research material. Based on the test results using the Weighted Moving Average method, it shows that the method runs well as expected. This can be proven by the calculation of MAD of 1.195 (gallons) and 0.792 (gas), MSE of 0.72 (gallons) and 0.34 (gas), and MAPE of 37.08 (gallons) and 33.2 (gas). So that the accuracy of test results can also be considered quite good.